Menumbuhkan Semangat Jiwa Wirausaha Pemuda Karang Taruna Pondok Ranggon – Jakarta Timur di Era Digital - Rosalina; Santi Octavia; Andi Primafira (Jurnal Abdimas Ekonomi dan Bisnis (JAmEB), 2022)
In today's Digital era, it is very important to build the business character or entrepreneurship of the younger generation. For them to have the awareness of changing the culture of 'job seeking' to a culture of 'creating jobs and jobs'. The spirit of the entrepreneur must be in the youth. One of them, built through carkater entreprenership by fostering new creative entrepreneurs who are innovative based on technology.The purpose of this activity is to empower Karang Taruna Pondok Ranggon – East Jakarta by providing Education and Motivation to grow their entrepreneurial spirit through a series of interactive presentations and discussions. The results of this activity show that this activity is able to increase and foster the entrepreneurial spirit of the youth so that they have a sense of interpreneuership and are able to see business opportunities.